Method for coating lipid on surface of DNA (deoxyribonucleic acid) nanostructure and constructed compound
By constructing a protective lipid biomitrotic layer on the surface of DNA nano -structural surface, the problem of being susceptible to nuclease degradation in the body by DNA nano -structures has improved its stability and application potential, and the drug stability and efficient delivery of drugs.
Patent Information
- Application Number
- CN202411501838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
DNA nanostructures are susceptible to nuclease degradation in the body, affecting their stability and function, and their foreign body properties may be recognized by the immune system, resulting in limited biomedical applications.
By constructing a protective lipid biomitrotic layer on the surface of DNA nano -structure, phospholipids modified by the arginine base group are connected to the phosphate group of DNA nanogenic structure, introduce phospholipids and form a hybrid lipid solution, and the DNA nano -structure.
It improves the physiological stability and blood circulation time of the DNA nano structure, reduce the stimulation of the immune system and the in vivo removal, and enhance its application potential in the drug therapy carrier, and reduce the construction cost.
Smart Images

Figure CN119367556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine and nanomaterials, and specifically relates to a method for coating lipids on the surface of a DNA nanostructure and a constructed lipid-DNA nanostructure complex. Background Art
[0002] DNA nanotechnology can be used to precisely design and assemble DNA nanostructures with various defined shapes. The high designability, encodeability, and spatial addressability of DNA nanostructures make it possible to precisely control and position assembly at the molecular scale, providing a powerful tool for personalized treatment. In addition, DNA nanotechnology can integrate multiple functions on a single platform, such as drug loading, targeted delivery, biosensing, etc., thereby improving the comprehensive performance of the DNA nanostructure platform system, which has a profound impact on promoting the development of biomedicine. However, the stability issues faced by DNA nanostructures have seriously restricted their biomedical applications. Although DNA nanostructures have a certain degree of stability in design, the complex environment in the body, especially the widespread nucleases in plasma, can gradually destroy their structure and affect their function. Nucleases can cause DNA nanostructures to degrade and disassemble, change their targeting, and make them lose their ability to carry drugs or inactivate drugs. In addition, the pH value, temperature, and ion concentration (low Mg) of the in vivo environment can also affect the stability of DNA nanostructures. 2+ ) and other factors may also cause changes in DNA nanostructures, affecting their stability and drug loading capacity. Although DNA nanostructures are biocompatible, their foreign properties may still be recognized by the immune system. Therefore, it is urgent to develop new coating technologies to block the impact of the body's complex environment on the DNA structure and achieve stable and efficient delivery of biotherapeutic agents (nucleic acids, therapeutic protein drugs).
[0003] For example, the patent document with publication number CN117899234A provides a liposome-DNA nanostructure complex and its preparation method and use. Although the liposome-nanostructure complex constructed by it solves the defects of using only liposomes or only DNA as drug delivery platforms in the prior art, the composite carrier constructed by it needs to design the cholesterol modification site of the DNA single strand end first. After the DNA single strands are assembled into DNA nanostructures, cholesterol is exposed to the surface of the DNA nanostructures, and finally embedded in the liposomes through cholesterol. When applied to other DNA nanostructures, it is necessary to re-sequence and modify the cholesterol site of some DNA single strands in the structure, which has high implementation cost and is not universal. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for coating lipids on the surface of DNA nanostructures in view of the deficiencies in the prior art. The method provided by the present invention is applicable to a variety of DNA nanostructures and can coat lipids on the surfaces of DNA nanostructures in different forms. The present invention constructs a protective lipid bilayer on the surface of the DNA nanostructure, and the lipid bilayer structure has excellent biocompatibility and stability. It is expected to solve the problem that the existing DNA nanostructures are susceptible to nuclease degradation, reduce the stimulation of the immune system, slow down their clearance rate in the body, and enhance the physiological stability of the DNA nanostructure, aiming to improve its versatility, reduce the construction cost of lipid-DNA nanostructure composite carriers, and enhance their application potential in drug treatment carriers.
[0005] Technical solution:
[0006] In a first aspect, the present invention provides a method for coating a surface of a DNA nanostructure with lipids, comprising the following steps:
[0007] Step 1, introducing a phospholipid modified with an arginine group to the surface of the DNA nanostructure through an ionic bond; the phospholipid modified with an arginine group is formed by connecting arginine Arg to the phospholipid structure through PEG;
[0008] Step 2: adding structural lipids, phospholipids, and PEG-converted lipids in proportion, forming rehydrated structural lipids, rehydrated phospholipids, and rehydrated PEG-converted lipids by thin film hydration method to prepare a mixed lipid solution;
[0009] Step 3: adding the mixed lipid solution to the DNA nanostructure solution obtained in step 1 to form a protective lipid bilayer on the surface of the DNA nanostructure.
[0010] Principle of the invention: Figure 1As shown, the arginine Arg in the phospholipid structure modified with the arginine group can be connected to the phosphate group of the DNA nanostructure through an ionic bond, thereby introducing a large amount of phospholipids on the surface of the DNA structure for subsequent recruitment of lipids on the surface of the DNA nanostructure and guiding lipid coating. And preferably, the phospholipid modified with the arginine group is DPA, which is DOPE-PEG-Arg, a structure formed by connecting arginine Arg to DOPE through PEG, and the corresponding Arg is connected to the phosphate group of the DNA nanostructure through an ionic bond, and then a large amount of lipid DOPE is introduced on the surface of the DNA nanostructure to recruit lipids and guide lipid coating; the material added subsequently for forming the lipid coating is the rehydrated mixed lipid solution added in step 2, and the mixed lipid solution includes rehydrated structural lipids, rehydrated phospholipids and rehydrated PEG conversion lipids, wherein the structural lipids serve as the coating lipid body, and the phospholipids serve as auxiliary lipids to mix the phospholipids that have been previously introduced on the surface of the DNA structure with the structural lipids, which helps to improve the membrane fusion of the nanolipids and maintain the stability of the lipid structure, and the PEG conversion lipids can make the surface of the nanolipids more compact, thereby achieving lipid coating on the surface of the DNA nanostructure.
[0011] The present invention utilizes the interaction between arginine and phosphate groups to connect lipids on the origami surface to achieve the coating of DNA nanostructures. It is expected to improve the physiological stability and blood circulation time of DNA nanostructures in the body and promote the enrichment of DNA nanostructures at the lesion.
[0012] As a preferred embodiment of the first aspect of the present application, the phospholipid modified with the arginine group is 1,2-dioleoyl-sn-glycerol-3-phosphatidylethanolamine-arginine DPA, and the DNA nanostructure is arranged every 100nm 2 For a unit surface area, the specific process of step 1 is as follows: adding DPA to the DNA nanostructure at a molar ratio of DPA to the unit surface area of the DNA nanostructure of 9.254:1, heating at 37°C for 1 hour, and removing excess DPA by ultrafiltration. Further preferably, the specific step of ultrafiltration is: using an ultrafiltration tube with a molecular weight cutoff of 100kD, centrifuging at a centrifugal force of 3000rcf for 10 minutes.
[0013] As a preferred embodiment of the first aspect of the present application, the structural lipid is (2,3-dioleoyl-propyl)-trimethylammonium chloride DOTAP, the phospholipid is 1,2-dioleoyl-sn-glycerol-3-phosphatidylethanolamine DOPE, and the PEG conversion lipid is 1,2-dimyristoyl-rac-glycerol-3-methoxypolyethylene glycol DMG-PEG;
[0014] Correspondingly, the specific process of step 2 is as follows: the lipid is dissolved in chloroform at a molar ratio of DOTAP:DOPE:DMG-PEG of 80:15:5, the lipid solution is dried using argon to form a lipid film, and then placed in a vacuum drying oven for 24 hours, water containing 1% n-octyl-β-D-pyranoglucoside OG is added to the dried lipid film, and ultrasonically rehydrated to form a rehydrated mixed lipid.
[0015] Accordingly, the specific process of step 3 is as follows: add the rehydrated mixed lipid with a molar mass of 1000 times that of the arginine group-modified phospholipid to the DNA nanostructure solution, heat at 37°C for 1 hour, and use a dialysis box with a molecular weight cutoff of 10 kD in 1×PBS-10 mM Mg 2+ The solution was dialyzed for 24 hours.
[0016] In a second aspect, the present invention provides a lipid-DNA nanostructure complex constructed by the method described in the first aspect. The DNA nanostructure includes origami structures of different forms constructed by DNA origami technology, such as rectangular DNA origami structures, triangular DNA origami structures, and tubular DNA origami; the DNA nanostructure also includes a DNA tetrahedral framework nucleic acid structure formed by self-assembly of DNA single strands, or other nanostructures formed based on self-assembly of DNA single strands.
[0017] Beneficial effects:
[0018] (1) The method for synthesizing lipid-coated DNA nanostructures of the present invention does not require modification of specific DNA chains, omits the cumbersome design steps in the traditional lipid-coated origami process, and connects lipids to the origami surface by utilizing the interaction between arginine and phosphate groups to achieve the coating of DNA nanostructures;
[0019] (2) This method is expected to provide a double protective barrier for the delivery of biotherapeutic agents through the organic combination of DNA nanostructures and lipids, thereby achieving stable and efficient drug transport. The drugs include nucleic acid drugs such as siRNA, antisense oligonucleotides, etc., which can be connected to the DNA nanostructure through the capture chain or extension chain on the DNA nanostructure in the form of base complementary pairing. The drugs also include therapeutic proteins such as tissue plasminogen activator, which can be covalently linked to the DNA rectangular origami. The rectangular nanosheets are curled and closed to form a nanotube structure through the design of the DNA lock chain to protect the activity of the drug. Since the drug is wrapped inside the nanotube structure, the lipid coating method of the present invention only coats the lipid on the outside of the nanotube structure, which will not affect the activity of the drug inside the nanotube structure, and the drug inside will not affect the stability of the coated lipid. The coating of liposomes is expected to slow down the external environment such as nucleases, low Mg 2+The environment degrades DNA nanostructures, improves their physiological stability and blood circulation time in the body, and promotes the enrichment of DNA nanostructures in lesions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the assembly process of coating lipids on the surface of a DNA nanostructure according to the present invention;
[0021] Figure 2 The transmission electron microscope characterization comparison diagram of rectangular origami before and after lipid coating, wherein, Figure a is the transmission electron microscope characterization of rectangular origami, and Figure b is the transmission electron microscope image of lipid-coated rectangular origami;
[0022] Figure 3 Figure 1 is a transmission electron microscope characterization comparison of a single sample observation view of rectangular origami before and after lipid coating, wherein Figure a is a partial enlarged view of a projection electron microscope image of rectangular origami, Figure b is a transmission electron microscope characterization of a single sample observation view of lipid-coated rectangular DNA origami synthesized in Example 1, and Figure c is a transmission electron microscope characterization of a single sample observation view of lipid-coated rectangular DNA origami synthesized in Example 2;
[0023] Figure 4 Figure 1 is an atomic force microscope characterization of DNA origami before and after lipid coating, wherein Figure a is an atomic force microscope (AFM) image of rectangular origami, Figure b is an atomic force microscope (AFM) image of lipid-coated rectangular DNA origami synthesized in Example 1, and Figure c is an atomic force microscope (AFM) image of lipid-coated rectangular DNA origami synthesized in Example 2;
[0024] Figure 5 Based on Figure 4 The three AFM characterization images in the figure show the height distribution analysis results of rectangular DNA origami before and after lipid coating;
[0025] Figure 6a The hydrated particle size distribution diagrams of rectangular DNA origami structures and lipid-coated rectangular DNA origami structures;
[0026] Figure 6b The zeta potential diagrams of rectangular DNA origami structures and lipid-coated rectangular DNA origami structures;
[0027] Figure 7 Figure 2 is a transmission electron microscopy characterization comparison of various DNA origami structures before and after being coated with lipids in Example 2, wherein Figure a is a rectangular DNA origami, Figure b is a triangular DNA origami, Figure c is a tubular DNA origami, Figure d is a lipid-coated rectangular DNA origami, Figure e is a lipid-coated triangular DNA origami, and Figure f is a lipid-coated tubular DNA origami structure;
[0028] Figure 8a Laser scanning confocal microscopy characterization of DNA tetrahedral framework nucleic acid structure;
[0029] Figure 8b Laser scanning confocal microscopy characterization of lipid-coated DNA tetrahedral framework nucleic acid structures;
[0030] Figure 8c This is the fluorescence signal characterization of the lipid-coated DNA tetrahedral framework nucleic acid structure of the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in detail below with reference to the accompanying drawings, but the protection scope of the present invention is not limited to the embodiments.
[0032] The raw materials and sources used in the following examples
[0033] Tris(hydroxymethyl)aminomethane (Tris), EDTA-2Na + ), magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O) and chloroform (CHCl3) were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; sodium chloride (NaCl) was purchased from Shanghai Titan Technology Co., Ltd.; potassium chloride (KCl) and n-octyl-β-D-pyranoglucoside (OG) were purchased from Anaiji (Shanghai) Pharmaceutical Chemistry Co., Ltd.; anhydrous dipotassium hydrogen phosphate (KH2PO4) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; (2,3-dioleoyl-propyl)-trimethylammonium chloride (DOTAP), 1,2-dimyristoyl-rac-glycero-3-methoxypolyethylene glycol 2000 (DMG-PEG 2000) and 1,2-dioleoyl-sn-glycerol-3-phosphatidylethanolamine (DOPE) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 1,2-dioleoyl-sn-glycerol-3-phosphatidylethanolamine-arginine (DPA) was purchased from Xi'an Ruixi Biotechnology Co., Ltd.; Dil cell membrane red fluorescent probe was purchased from Biyuntian Biotechnology Co., Ltd.; uranyl acetate was purchased from Henan Ruixin Laboratory Supplies Co., Ltd.; Slide-A-Lyzer dialysis cassette (molecular weight cutoff: 10kD) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; millipore ultrafiltration tube (molecular weight cutoff: 100kD) was purchased from Merck, USA; M13mp18 was purchased from NEB; all DNA short chains in DNA origami were purchased from Shanghai Sangon Biotechnology Co., Ltd.; all experimental water was ultrapure water.
[0034] Preparation of DNA Nanostructures
[0035] In the following embodiments, rectangular DNA origami structures, triangular DNA origami structures, tubular DNA origami and tetrahedral framework nucleic acid structures are specifically used as examples to illustrate the lipid coating method of the present invention, but the DNA nanostructures used in the present invention are not limited to these four types and the preparation process is not limited to the following preparation process.
[0036] 1) The rectangular DNA origami structure, triangular DNA origami structure and tubular DNA origami structure specifically used in the following examples all include an M13mp18 template chain and a DNA staple chain, wherein the nucleotide sequence of the M13mp18 phage genomic DNA is provided in GenBank: X02513.1 and purchased from Biobio Biotech Co., Ltd., with a product number and specification of B3003-50 pmol.
[0037] The sequence design of the rectangular DNA origami structure is selected from the design of the Bridged seam rectangle in the literature “Folding DNA to create nanoscale shapes and patterns” of DOI:10.1038 / nature04586;
[0038] The sequence design of the DNA staple strands of the triangular DNA origami structure was selected from the design of triangular origami staple strands in the literature “DNA directed self-assembly of anisotropic plasmonic nanostructures” with DOI:10.1021 / ja207898r;
[0039] The sequence design of the DNA staple chain of the tubular DNA origami structure was selected from the design of Original nanotubes with 18 connections in the literature “Single-step rapid assembly of DNA origaminanostructures for addressable nanoscale bioreactors” with DOI:10.1021 / ja3076692;
[0040] The rectangular DNA origami structure, the triangular DNA origami structure and the tubular DNA origami structure have the same raw materials and preparation processes except for the different staple chains. The specific preparation processes are as follows:
[0041] The M13mp18 template strand and DNA staple strand were in 1×TAE-Mg 2+The buffer was mixed in a PCR tube at a final concentration of 100 nM and 500 nM respectively; the mixture was slowly annealed using a gradient thermal cycler, and the annealing conditions were as follows: the starting point temperature was set at 95°C and maintained for 3 minutes, followed by gradient cooling, the end point temperature was 25°C, and each 1°C drop was a gradient, and each gradient stayed for 100 s to obtain the above-mentioned different forms of DNA origami structures; after the annealing procedure was completed, the PCR tube was taken out and ultrafiltration centrifuged using a millipore ultrafiltration tube (molecular weight cutoff: 100 kD) to remove excess DNA short chains, and the centrifugation conditions were as follows: 1×TAE-Mg 2+ The sample volume was filled to 400 μL with buffer, centrifuged at 3000 rcf for 10 minutes, and repeated three times; the inner tube of the ultrafiltration tube was inverted into the outer tube, and centrifuged at 1000 rcf for 10 minutes. The rectangular DNA origami constructed was about 90 nm long and 60 nm wide, showing a regular rectangular structure; the triangular DNA origami structure constructed was about 120 nm long, showing a regular equilateral triangle structure; the tubular DNA origami structure constructed was about 90 nm long and 20 nm in diameter, showing a regular tubular structure.
[0042] The DNA sequence was purchased from Bio-Technology Co., Ltd.
[0043] 2) The DNA sequence used to synthesize the DNA tetrahedral framework nucleic acid structure is as follows (5'–3'):
[0044] The S1 extended chain is shown in SEQ ID NO. 1 in the sequence listing: TTT TTACTCAAC TGC CTG GTGATACGAGGATGG GCATGC TCT TCC CGACGG TAT TGGACC CTC GCATG
[0045] The S2 extended chain is shown in SEQ ID NO. 2 in the sequence listing: TTT TTACGATTACAG CTT GCTACACGATTCAGACTTAGGAAT GTT CGACAT GCGAGG GTC CAATAC CG
[0046] The S3 extended chain is shown in SEQ ID NO. 3 in the sequence listing: TTT TTACTACTATGG CGG GTGATA AAACGTGTAGCAAGC TGTATT CGACGG GAAGAG CAT GCC CAT CC
[0047] The extended chain of FAM-S4 is shown in SEQ ID NO.4 in the sequence listing: TTT TTATTTATCACC CGC CATAGTAGACGTATCACCAGG CAG TTGAGACGAACATTC CTAAGT CTGAA
[0048] The above DNA sequences were purchased from Sangon Biotechnology (Shanghai) Co., Ltd.
[0049] The specific preparation process of the DNA tetrahedral framework nucleic acid structure is as follows: First, the DNA chains required for synthesis are quantified by UV-visible spectroscopy, and the S1 extended chain, S2 extended chain, S3 extended chain, and S4 extended chain labeled with FAM fluorescent dye (FAM-S4 extended chain) are added to TM (pH 8.0, containing 5mM Mg) at a molar ratio of 1:1:1:1. 2+ ) buffer, placed in a thermal cycler and heated to 95°C, maintained for 5 to 10 minutes, and then quickly cooled to 4°C within 30 seconds to obtain a DNA tetrahedral framework nucleic acid.
[0050] Example 1 Preparation of lipid-coated DNA nanostructures (500:1)
[0051] By DPA:100nm 2 DNA nanostructure = 9.254:1 ratio, add DPA to the DNA nanostructure solution and mix, place the mixed solution in a shaker and incubate at 37°C for 1 hour, the arginine group of DPA is connected to the phosphate group present in large quantities on the DNA nanostructure through a salt bridge bond, so that a large amount of lipid DOPE is distributed on the surface of the DNA nanostructure, which serves as the connection point for the lipid coating on the DNA nanostructure later. After the reaction is completed, take out the solution in the PCR tube and use a millipore ultrafiltration tube (molecular weight cutoff: 100kD) for ultrafiltration to remove unbound DPA. The ultrafiltration conditions are: use 1×PBS-Mg 2+ (Contains 10 mM Mg 2+ ) buffer was added to make up the sample volume to 400 μL, and the sample was centrifuged at 3000 rcf for 10 minutes, and the centrifugation was repeated 3 times; the inner tube was inverted into the outer tube, and the sample was centrifuged at 1000 rcf for 10 minutes to finally obtain DOPE-modified DNA nanostructures.
[0052] The lipids DOTAP, DOPE and DMG-PEG were added to chloroform at a molar ratio of 80:15:5, and the mixed lipid solution was slowly blown dry with argon gas, and then placed in a vacuum drying oven for 24 hours to ensure that the chloroform in the lipid solution was removed. Ultrapure water containing 1% OG was added to the dried lipids, in which the OG component helps the lipids to dissolve in water, and the solution was sonicated to obtain a rehydrated lipid solution. The mixed lipid solution and DPA were mixed at a molar ratio of 500:1 and 1000:1, respectively, and the mixed solution was placed in a shaker and incubated at 37°C for 1 hour to coat the lipids on the surface of the DNA nanostructure. Finally, a dialysis box with a molecular weight cutoff of 10kD was used in 1×PBS-Mg 2+ (Contains 10 mM Mg 2+ ) buffer for 24 h to obtain lipid-coated DNA nanostructures.
[0053] Example 2 Preparation of lipid-coated DNA nanostructures (1000:1)
[0054] The only difference between Example 2 and Example 1 is that the mixed lipid solution and DPA are mixed at a molar ratio of 1000:1, and the remaining preparation steps and conditions are the same as those in Example 1.
[0055] Characterization Example 1: Transmission electron microscopy characterization comparison of DNA origami before and after lipid coating
[0056] Wash with 1× PBS-Mg 2+ (Contains 10 mM Mg 2+ ) Dilute the DNA origami solution before and after lipid coating. Take 10 μL of the diluted sample and drop it on the copper mesh, let it stand for 10 minutes, then remove the droplets by suction, then take 10 μL of 1% uranyl acetate solution and drop it on the copper mesh, let it stand for 5 minutes to stain the sample. Then remove the droplets by suction, and rinse the copper mesh with 10 μL of ultrapure water. Repeat twice, remove the droplets by suction, let it stand for one day to dry, and finally characterize the sample on the copper mesh using a transmission electron microscope.
[0057] Figure 2 Comparison of transmission electron microscopy characterizations of rectangular origami before and after lipid coating, wherein Figure a is a transmission electron microscopy image of the rectangular origami prepared as described above, and Figure b is a transmission electron microscopy image of the rectangular origami after lipid coating in Example 2; the size and contrast of the rectangular origami increased after lipid coating, forming a nearly spherical structure, verifying the successful coating of lipids on its surface.
[0058] Figure 3Comparison of transmission electron microscopy characterizations of single sample observation views of rectangular origami before and after lipid coating, wherein Figure a is a partial enlarged view of the projection electron microscopy image of the rectangular origami, Figure b is a transmission electron microscopy characterization of a single sample observation view of the lipid-coated rectangular DNA origami synthesized in Example 1, and Figure c is a transmission electron microscopy characterization of a single sample observation view of the lipid-coated rectangular DNA origami synthesized in Example 2; as shown in Figure b, the shape of the sample with mixed lipid solution: DPA=500:1 still maintains a rectangle, but the coating is incomplete and the contrast is uneven; as shown in Figure c, the contrast of the sample with mixed lipid solution: DPA=1000:1 is higher, and the shape changes from rectangular to nearly circular, which can achieve more efficient lipid coating, and subsequent samples will also be prepared and characterized using the lipid solution: DPA=1000:1 method.
[0059] Figure 7 Figure 2 is a comparison of transmission electron microscopy images of various DNA origami structures before and after being coated with lipids in Example 2, wherein Figure a, Figure b, and Figure c are transmission electron microscopy images of rectangular DNA origami structures, triangular DNA origami structures, and tubular DNA origami, respectively; Figure d, Figure e, and Figure f are transmission electron microscopy images of rectangular DNA origami structures, triangular DNA origami structures, and tubular DNA origami coated with lipids of the present invention, respectively; Figure 7 It can be seen that for various DNA nanostructures of different forms, their structures after lipid formation are similar to those before formation, and their sizes and contrasts have increased, proving the successful coating of lipids. It also proves the versatility of this method, providing a simple and universal strategy for lipid coating of DNA materials with different structures.
[0060] Characterization Example 2: Atomic force microscopy characterization of DNA origami before and after lipid coating
[0061] Wash with 1× PBS-Mg 2+ (Contains 10 mM Mg 2+ ) Dilute the rectangular DNA origami structure and the lipid-coated rectangular DNA origami structure respectively. Fix the cut new mica sheet on the flat iron sheet with double-sided tape, and then peel the mica sheet until the surface is flat. The flat mica sheet can ensure the accuracy of atomic force microscope imaging; add 8μL of sample solution to the mica sheet with a flat surface, let it stand for 15 minutes, rinse the mica sheet with ultrapure water to remove impurities and unabsorbed samples, and blow dry with an ear bulb. Impurities and water quality on the mica sheet that have not been removed will cause inaccurate imaging; place the mica sheet with the attached sample on the sample stage of the atomic force microscope and scan it at a scanning frequency of 1Hz. The results are as follows: Figure 4 As shown, Figure 4That is, the atomic force microscopy characterization of DNA origami before and after lipid coating, wherein Figure a is an atomic force microscopy (AFM) image of rectangular origami, Figure b is an atomic force microscopy (AFM) image of lipid-coated rectangular DNA origami synthesized in Example 1, and Figure c is an atomic force microscopy (AFM) image of lipid-coated rectangular DNA origami synthesized in Example 2. Figure 4 The AFM images in the figure show the height distribution analysis of the rectangular DNA origami before and after lipid coating. The height distribution comparison analysis results are shown in the figure below. Figure 5 As shown, the sample with lipid solution:DPA=1000:1 is taller, with the highest height being about 30nm; the sample with lipid solution:DPA=500:1 is incompletely coated, with the highest height being about 15nm; the rectangular DNA origami coated with lipids is more than 100nm long; the height of the rectangular DNA origami is about 2nm and the length is about 90nm.
[0062] Characterization Example 3: Dynamic light scattering and zeta potential characterization of rectangular DNA origami before and after lipid coating
[0063] The dynamic light scattering results show Figure 6a It can be seen that the average hydrodynamic diameter of the rectangular DNA origami is about 93.97nm, and its average hydrodynamic diameter increases to about 189.12nm after being coated with lipids. DNA molecules show negative charge due to the negative charge of their phosphate backbone, and the zeta potential of the rectangular DNA origami coated with lipids increases from -20.67±1.62mV to -11.71±0.83mV. This increase may be due to the fact that the positive charge of the lipid partially neutralizes the negative charge of the phosphate backbone of the DNA molecule, such as Figure 6b shown.
[0064] Characterization Example 4: Characterization of DNA Tetrahedral Framework Nucleic Acid Structure Before and After Lipid Coating
[0065] Laser scanning confocal microscopy was used to verify the lipid coating of the DNA tetrahedron framework nucleic acid structure. The laser emitted two different wavelengths of laser light, and the digital image acquisition and processing were carried out through the control of the conjugate focusing device and computer, and the specific positions of the two fluorescences were observed, and the DNA tetrahedron and liposome were located respectively. The DNA tetrahedron was modified with FAM fluorescent group, the excitation wavelength was 488nm, and the receiving wavelength of the confocal microscope was set to 508-608nm. The lipid was stained with Dil fluorescent dye, the excitation wavelength was 559nm, and the receiving wavelength of the microscope was set to 579-679nm. Figure 8a This is a laser scanning confocal microscope photo of the DNA tetrahedral framework nucleic acid structure. Figure 8b Laser scanning confocal microscopy characterization of lipid-coated DNA tetrahedral framework nucleic acid structures; Figure 8cAs shown, the lipid fluorescence signal stained with the red fluorescent probe on the Dil cell membrane coincides with the fluorescence signal of the FAM group modified on the DNA tetrahedron, proving that the lipid successfully coated the DNA tetrahedron framework nucleic acid structure.
[0066] In summary, the synthesis method of the lipid-coated DNA nanostructure constructed by the present invention is applicable to DNA nanostructures of different forms.
[0067] Finally, it should be noted that the above description is only an embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for coating a surface of a DNA nanostructure with lipids, characterized in that: The following steps are involved: Step 1: introducing a phospholipid modified with an arginine group onto the surface of the DNA nanostructure via an ionic bond; the phospholipid modified with an arginine group is formed by connecting arginine Arg to a phospholipid structure via PEG; Step 2: adding structural lipids, phospholipids, and PEG-converted lipids in proportion, forming rehydrated structural lipids, rehydrated phospholipids, and rehydrated PEG-converted lipids by thin film hydration method to prepare a mixed lipid solution; Step 3: adding the mixed lipid solution to the DNA nanostructure solution obtained in step 1 to form a protective lipid bilayer on the surface of the DNA nanostructure.
2. A method for coating lipids on the surface of a DNA nanostructure according to claim 1, characterized in that: The phospholipid modified with the arginine group is DPA.
3. A method for coating lipids on the surface of a DNA nanostructure according to claim 2, characterized in that: The specific steps of step 1 are: adding DPA to the DNA nanostructure at a molar ratio of DPA to DNA nanostructure per unit surface area of 9.254:1, heating at 37° C. for 1 hour, and removing excess DPA by ultrafiltration.
4. A method for coating lipids on the surface of a DNA nanostructure according to claim 3, characterized in that: The specific steps of the ultrafiltration are: using an ultrafiltration tube with a molecular weight cutoff of 100 kD, and centrifuging at a centrifugal force of 3000 rcf for 10 minutes.
5. The method for coating a surface of a DNA nanostructure with lipid according to claim 1, characterized in that: The structural lipid is DOTAP, the phospholipid is DOPE, and the PEG conversion lipid is DMG-PEG.
6. A method for coating lipids on the surface of a DNA nanostructure according to claim 5, characterized in that: The specific steps of step 2 are as follows: dissolving lipids in chloroform at a molar ratio of DOTAP:DOPE:DMG-PEG of 80:15:5, drying the lipid solution with argon gas to form a lipid film, and then drying the lipid film in a vacuum drying oven for 24 hours, adding water containing 1% OG to the dried lipid film, and rehydrating it by ultrasound to form a rehydrated mixed lipid; The specific steps of step three are as follows: adding a rehydrated mixed lipid with a molar mass of 1000 times that of the arginine group-modified phospholipid to the DNA nanostructure solution, heating at 37°C for 1 hour, and using a dialysis cassette with a molecular weight cutoff of 10 kD in 1×PBS-10 mM Mg 2+ The solution was dialyzed for 24 hours.
7. The lipid-DNA nanostructure complex constructed by the method according to any one of claims 1 to 6.
8. Use of the lipid-DNA nanostructure complex according to claim 7 in preparing a delivery vector for a biological therapeutic agent.
Citation Information
Patent Citations
Liposome-DNA (Deoxyribose Nucleic Acid) nanostructure compound as well as preparation method and application thereof
CN117899234A